The impact of chronic kidney disease and cardiovascular comorbidity on mortality in a multiethnic population: a retrospective cohort study. Issue 12 (3rd December 2013) - Jesky, Mark; Lambert, Amanda; Burden, A C Felix; Cockwell, Paul
Abstract : Objective: To assess the impact of chronic kidney disease (CKD) and cardiovascular comorbidity on mortality in a multiethnic primary care population. Design: Retrospective cohort study. Setting: Inner-city primary care trust in West Midlands, UK. Participants: Individuals aged 40 years and older, of South Asian, black or white ethnicity, registered with a general practice and with their kidney function checked within the last 12 months (n=31 254). Outcome measure: All-cause mortality. Results: Reduced estimated glomerular filtration rate, higher albuminuria, older age, white ethnicity (vs South Asian or black ethnicity) and increasing cardiovascular comorbidities were independent determinants of a higher mortality risk. In the multivariate model including comorbidities and kidney function, the HR for mortality for South Asians was 0.697 (95% CI 0.56 to 0.868, p=0.001) and for blacks it was 0.533 (95% CI 0.403 to 0.704, p<0.001) compared to whites. Conclusions: The HR for death is lower for South Asian and black individuals compared to white individuals. This is, in part, independent of age, gender, socioeconomic status, kidney function and comorbidities. Risk of death is higher in individuals with CKD and with a higher cumulative cardiovascular comorbidity.